Recycling graphene from supercapacitor electrodes as reinforcing filler for epoxy resins - Jiang, Guozhan; Pickering, Stephen J. (Springer, 2017)
A wet shredding process has been developed for recycling graphene from the electrodes of supercapacitors into polymer composites. At first, supercapacitors are cut open to expose the interior graphene based electrodes. The electrodes are heat-treated at 200o C to remove the contained solvent, and the heat treatment temperature can be further increased to remove the polymer binder, which binds the graphene on an aluminium foil current collector. After heat treatment, the electrodes are shredded in an epoxy resin to strip off the graphene and the graphene was subsequently dispersed using a high shear mixer. The dispersed graphene is used directly as reinforcing filler for the epoxy resin. A content of 0.40% (wt) of the recycled graphene resulted in a significant increase in both the tensile strength and elongation at break of the epoxy resin. Removal of the binder increases the reinforcing effect of the recycled graphene. However, a compromise can be made to leave the binder in the recycled graphene in order to avoid secondary pollution.